2020
DOI: 10.1186/s12874-020-01047-2
|View full text |Cite
|
Sign up to set email alerts
|

Research methodology and characteristics of journal articles with original data, preprint articles and registered clinical trial protocols about COVID-19

Abstract: Background: The research community reacted rapidly to the emergence of COVID-19. We aimed to assess characteristics of journal articles, preprint articles, and registered trial protocols about COVID-19 and its causal agent SARS-CoV-2. Methods: We analyzed characteristics of journal articles with original data indexed by March 19, 2020, in World Health Organization (WHO) COVID-19 collection, articles published on preprint servers medRxiv and bioRxiv by April 3, 2010. Additionally, we assessed characteristics of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 12 publications
2
41
0
2
Order By: Relevance
“…Since there has been insufficient time to design, approve, conduct, and conclude such studies, reports of preliminary results can be expected over the upcoming months. A previous cross-sectional study on COVID-19-related publications revealed that only a quarter of the first 2118 articles contained original data [31]. In our study, the number of registered trial protocols listed as "ongoing" in Clinicaltrials.gov and in ChiCTR (n = 795 and n = 308, respectively) signals an upward trend.…”
Section: Plos Onesupporting
confidence: 46%
“…Since there has been insufficient time to design, approve, conduct, and conclude such studies, reports of preliminary results can be expected over the upcoming months. A previous cross-sectional study on COVID-19-related publications revealed that only a quarter of the first 2118 articles contained original data [31]. In our study, the number of registered trial protocols listed as "ongoing" in Clinicaltrials.gov and in ChiCTR (n = 795 and n = 308, respectively) signals an upward trend.…”
Section: Plos Onesupporting
confidence: 46%
“…Approximately 900 articles, including published works and preprints, were published prior to March 12, 2020 (Callaway et al, 2020). A signi cant proportion of the preprint surge could be a result of scholarly journals requiring that works submitted for peer-review must be made simultaneously available for the public on a preprint server (Fidahic, Nujic, Runjic, Civljak, Markotic, Lovric Makaric, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, due to the sanitary emergency, authors have been urged to share relevant information as soon as possible, thus, an increasing amount of studies have been posted as preprints (Rubin et al, 2020). As well, many scholarly journals have required that authors share their work initially in a preprint server, before it goes through peer-review and editing processes (Fidahic, Nujic, Runjic, Civljak, Markotic, Lovric, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same arguments can be used for health sciences education. However, despite the explosion of research about COVID-19 [14], few studies have been devoted to exploration of radical changes that the pandemic imposed in medical and health sciences education.…”
Section: Discussionmentioning
confidence: 99%